Clinical and Ultrasonographic evaluation of patients with Trochanteric Bursitis - Hikmet Hameed, Ibtihal; A AlBustany , Dashti (Diyala Journal of Medicine, 2022)
Background: Trochanteric bursitis is an inflammation of the greater trochanteric bursa which is a recurrent source of lateral hip pain. Objective: To assess the diagnostic value of 6 clinical tests that can be used to diagnose trochanteric bursitis and utilize ultrasound as an imaging modality to confirm the diagnosis. Patients and Methods: This Cross-sectional study included 85 consecutive patients who had been experienced lateral hip pain in the greater trochanteric area for at least 6 weeks with at least one of the following features: pain on lying on the affected side, pain while climbing stairs or when sitting. Six clinical tests on examination that elicit pressure on the greater trochanteric region were performed to evaluate their value to diagnose trochanteric bursitis and then ultrasound was utilized to confirm the diagnosis. Results: A total of 85 participants were enrolled in the study. Tenderness to deep palpation was the most accurate sign in predicting the diagnosis, with a sensitivity of 100% and specificity of 81.8%. There were no significant differences between its results and the ultra-sonographic findings (p=0.500). Regarding the other tests, there were significant differences between their results and the results of ultrasound (p< 0.001). Conclusion: Tenderness to deep palpation of the greater trochanter, combined with ultrasound imaging modality, is likely to have the best diagnostic value for evaluation of trochanteric bursitis in patients complaining of lateral hip pain around the greater trochanter region.